2021
DOI: 10.1088/2631-8695/abf9e5
|View full text |Cite
|
Sign up to set email alerts
|

Design of metal hydride reactor with embedded helical coil using optimization methods

Abstract: Metal hydride offers an efficient and cost-effective method to store hydrogen. In this study, Taguchi method coupled with grey relational analysis was used to optimize the design parameters i.e., diameter of helical tube (dh), major diameter of helical tube (dm), number of turns of helical tube (N) and velocity of heat transfer fluid ( V f ) for the helical tube heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…The above model is a combination of two reactors that are validated individually in previous articles of other authors. 27,28 The individual models are closely matching with the experimental studies with a maximum variation of 5.24% and 2.4% for Mg 2 Ni−H 2 and LaNi 5 −H 2 respectively. Since these two validated models are used further for the combined system, it is expected that the present model gives a good approximation.…”
Section: ( ) P E P G P Msupporting
confidence: 75%
See 2 more Smart Citations
“…The above model is a combination of two reactors that are validated individually in previous articles of other authors. 27,28 The individual models are closely matching with the experimental studies with a maximum variation of 5.24% and 2.4% for Mg 2 Ni−H 2 and LaNi 5 −H 2 respectively. Since these two validated models are used further for the combined system, it is expected that the present model gives a good approximation.…”
Section: ( ) P E P G P Msupporting
confidence: 75%
“…The water is used as HTF in this reactor as the temperature of reactor is below boiling point of water. The dimension of Reactor B and geometrical parameters of helical tube was optimized by Taguchi analysis and Grey relational analysis in the previous article . The design and dimensions correspond to minimum time for hydrogen desorption is selected and given in Table .…”
Section: System Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently few scientic literature studies have been published on the implementation of the Taguchi method and Grey relational analysis for optimal system design with different enhancement techniques. [42][43][44] It was found that the Taguchi method and Grey relational analysis have limitations in terms of the selection of parameters and their levels, wherein global optimization with large sets of parameters is difficult to attain. 45,46 Nowadays machine learning along with various optimization techniques is at the forefront in various disciplines to optimize large datasets with a higher number of parameters.…”
Section: Sustainablementioning
confidence: 99%
“…6a) are also essential factors affecting the effect of the MHR with spiral tubes thermal management besides the parameters of number, size, and position. 48,[65][66][67][68][69][70] The major radius reects the distance from the center of the MHB to the spiral tubes, and the axial pitch is dened as the distance between similar positions on consecutive turns of the spiral tubes. The reaction rate is accelerated by growing the major radius and the number of spiral tube turns, whereas a rise in axial pitch has the reverse effect on H 2 absorption.…”
Section: Addition Of Cooling Devicesmentioning
confidence: 99%